Cooperative Cognitive Radio Sensing - Optimization: status, challenges and future Trends - Mohammed, Doaa A.; Sadkhan, Sattar B. (2021 1st Babylon International Conference on Information Technology and Science (BICITS), 2021)
Cognitive-Radio (CR) is a technique that has revolutionized the information technology market to improve the use of the electromagnetic spectrum. Spectrum sensing is an essential component of CR to avoid conflict problems with primary users and define available spectrum to maximize spectrum utilization. however, problems with multipath fading, shadowing, and uncertainty also undermine detection effectiveness. cooperative spectrum sensing has proven to be an Efficient tool for these problems by exploiting spatial diversity so improving detection efficiency. A literature review, framework and elements of cooperative sensing, classification of cooperative sensing, and various optimization of cognitive radio are discussed in this article.